EFEKTIVITAS METODE PEMBELAJARAN SCL (STUDENT CENTERED LEARNING) DAN TCL (TEACHER CENTERED LEARNING) PADA MOTIVASI INSTRINSIK & EKSTRINSIK MAHASISWA PSIKOLOGI UNTAG SURABAYA ANGKATAN TAHUN 2014 – 2015 - Ramadhani, Hetti Sari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract His study aims to see the effectiveness of learning methods scl (student center learning) and tcl (teacher center learning) on intrinsic & extrinsic motivation student psychology UNTAG Surabaya Year 2014-2015. The research subjects took random sampling of 100 students from the class of 2014 and 2015. The intrinsic and extrinsic motivation scales used consisted of 21 valid and reliable items. The data were analyzed using Independent Sample T Test test which had previously tested normality and homogeneity. Based on the calculation result known Sig value. 0,946> 0,05 meaning that there is no difference of intrinsic motivation and extrinsic motivation at UNTAG student of psychology class of 2014 and 2015 which received learning method scl (student center learning) and tcl (teacher center learning). Keyword: intrinsic & extrinsic motivation, scl (student center learning) and tcl (teacher center learning)